New Results on Impulsive Functional Differential Equations with Infinite Delays - Jie Yang; Bing Xie (Abstract and Applied Analysis)
We investigate the stability for a class of impulsive functional differential equations with infinite delays by using Lyapunov functions and Razumikhin-technique. Some new Razumikhin-type theorems on stability are obtained, which shows that impulses do contribute to the system’s stability behavior. An example is also given to illustrate the importance of our results.